Awareness as a dimension of health care access: exploring the case of rural palliative care provision in Canada. Issue 2 (April 2019) - Pugh, Arlanna; Castleden, Heather; Giesbrecht, Melissa; Davison, Colleen; Crooks, Valorie
Objectives: In Canada, the rural elderly population is increasing in size, as is their need for palliative care services in these settings. This analysis aims to identify awareness-associated barriers to delivering rural palliative care services, along with suggestions for improving service delivery from the perspective of local health care providers. Methods: A total of 40 semi-structured interviews with various formal and informal health care providers were conducted in four rural and/or remote Canadian communities with limited palliative care resources. Interview data were thematically coded using Penchansky and Thomas' five dimensions of access (i.e. availability, (geographic) accessibility, accommodation, acceptability and affordability). Saurman's recently added sixth dimension of access – awareness – was also identified while coding and subsequently became the primary focus of this analysis. Results: Identified barriers to palliative care awareness and suggestions on how to enhance this awareness, and ultimately palliative care delivery, corresponded with three key themes arising from the data: limited palliative care knowledge/education, communication and coordination. Participants recognized the need for more palliative care education, open lines of communication and better coordination of palliative care initiatives and local resources in their communities. Conclusions: These findings suggest that identifying the barriers to palliative care awareness in rural communities may be foundational to addressing barriers to the other five dimensions of access. A thorough understanding of these three areas of awareness knowledge, communication and coordination, as well as the connections between them, may help enhance how rural palliative care is delivered in the future.